Heterothallic species of Neurospora are distinguishable by restriction analysis of their nuclear r-DNA sequences. - C. Chambers; S. K. Dutta (Fungal Genetics Reports, 1983)
Heterothallic species of Neurospora are distinguishable by restriction analysis of their nuclear rDNA sequences.